Fundamentals of information technology - Bharihoke, Deepak (New Delhi Pentagon, 2000)
This book is a self contained introduction to computers and cumputing. The main objective of the book is to provide the understanding of fundamental concepts of computer and computer technologies.The book covers computer concepts,Input/Output devices,data
Keywords: Computer architecture; Computer input-output equipment; Computer networks; Computer science; Computer software-Development